Geekerella ebook A fangirl fairy tale. - Poston, Ashley (Once Upon a Con, 2017)
Cinderella goes to the con in this charming young adult romance that puts a fandom twist on the classic fairy tale —from a New York Times bestselling author! “With geekily adorable characters, a show that’s part Star Trek and part Firefly , a cosplay contest, and a food truck fairy godmother, this is a love letter to fandom.” — Booklist Geek girl Elle Wittimer lives and breathes Starfield , the classic sci-fi series she grew up watching with her late father. So when she sees a cosplay contest for a new Starfield movie, she has to enter. The prize? An invitation to the ExcelsiCon Cosplay Ball, and a meet-and-greet with the actor slated to play Federation Prince Carmindor in the reboot. With savings from her gig at the Magic Pumpkin food truck (and her dad’s old costume), Elle’s determined to win . . . unless her stepsisters get there first.   Teen actor Darien Freeman used to live for cons—before he was famous. Now they’re nothing but autographs and awkward meet-and-greets. Playing Carmindor is all he’s ever wanted, but the Starfield fandom has written him off as just another dumb heartthrob. As ExcelsiCon draws near, Darien feels more and more like a fake—until he meets a girl who shows him otherwise.   Part romance, part love letter to nerd culture, and all totally adorbs, Geekerella is a fairy tale for anyone who believes in the magic of fandom.